2017
DOI: 10.2147/jpr.s129295
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characteristics, and burden of failed back surgery syndrome: the influence of various residual symptoms on patient satisfaction and quality of life as assessed by a nationwide Internet survey in Japan

Abstract: We conducted a cross-sectional, Internet-based survey with a nationally representative sample of Japanese adults to assess the prevalence and characteristics of failed back surgery syndrome (FBSS). Data regarding the residual symptoms and patient satisfaction from an online survey of 1842 lumbar surgery patients revealed the prevalence of FBSS to be 20.6% (95% confidence interval [CI], 18.8–22.6). The prevalence of low back pain, dull ache, numbness, cold sensations, and paresthesia after surgery was 94.0%, 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 29 publications
(28 reference statements)
0
35
0
4
Order By: Relevance
“…All patients attained radiological fusion at 12 months with 18 (60%) meeting the Ray's criteria of bony healing at 6-month follow-up (Figs. [3][4][5].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients attained radiological fusion at 12 months with 18 (60%) meeting the Ray's criteria of bony healing at 6-month follow-up (Figs. [3][4][5].…”
Section: Resultsmentioning
confidence: 99%
“…Early failure is generally due to poor patient selection, improper procedure, or infection (discitis). A new onset of pain following good surgical results may be due to recurrent disc herniation, instability of the operated segment, or affection at a different disc level [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Using internet-based survey data, the authors found that among 1842 respondents who self-reported having undergone lumbar surgery in the past 10 years, 20.6% experienced ongoing pain. 29 strengths and limitations of this study This study used routinely captured hospital and primary care data to investigate diagnoses and treatment patterns on a population sample of lumbar surgery patients. Hence, our observations are based on patterns of care for a large and representative group of patients undergoing treatment in real-world settings.…”
Section: Discussionmentioning
confidence: 99%
“…Failed Back Surgery Syndrome (FBSS) is characterized by persisting back and/or leg pain of unknown origin either persisting despite surgical intervention or appearing after surgical intervention for spinal pain [ 1 ]. FBSS affects between 10 and 40% of patients following back surgery, resulting in more pain, increased opioid use, disability, and lower quality of life [ 2 , 3 ]. In comparison to other common chronic pain and medical conditions, the impact of FBSS on an individual’s health-related quality of life (HRQoL) and its socio-economic burden are considerably higher [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%